Detection of Toxocara cati Larvae from Ostrich and Wild Boar Meat Intended for Human Consumption - Alice Michelutti; Sofia Sgubin; Christian Falcaro; Valentina Cagnin; Alessia Zoroaster; Patrizia Danesi (Pathogens, 2021)
Toxocara cati is a common roundworm of cats and wild felids and, together with T. canis, it is the main causative agent of human toxocariasis. Humans may become infected by ingestion of embryonated eggs via contaminated soil, food, or water, or by ingestion of raw or undercooked meat of paratenic hosts that are infected by Toxocara larvae. In this study, we report the detection of T. cati larvae from meat samples of ostriches and wild boars. These samples were inspected by enzymatic digestion, as part of the trichinellosis surveillance. As ostrich meat is intended for “carpaccio” preparation, a traditional Italian raw meat preparation, there is the need to make the consumption of this meat safe. For this purpose, it is recommended to freeze the meat before preparation. Our findings confirmed that T. cati larvae can contaminate muscle tissues of paratenic hosts, increasing the risk of infection due to the consumption of raw or undercooked meat.